Membangun Kesadaran Santri Terhadap Bahaya Mengkonsumsi Produk Mengandung Perasa, Pewarna, Pengawet Dan Penyedap (P4) di Dayah Jamiah Al-Aziziyah Samalanga Kabupaten Bireuen - Abdurrauf, Mursal (Yayasan Madinah Al-Aziziyah, 2023)
This research was conducted to increase the awareness of students (santri) regarding the dangers of products containing p4 at Dayah Jamiiah Al-Aziziyah Samalanga in Bireuen Regency. This is a qualitative (field research) study. The analysis revealed that the research was aimed at increasing the awareness of santri regarding the dangers of p4-containing products at Dayah Jamiiah Al-Aziziyah Samalanga in Bireuen Regency. The stages included preparation and implementation of the research. In its implementation, the researchers planned a program, provided education in the Dayah Jamiiah Al-Aziziyah hall, monitored the students at the sales points, provided understanding to sellers in the Dayah Jamiiah Al-Aziziyah area, created stickers and banners about the dangers of p4-containing food products and the importance of maintaining a healthy lifestyle, built awareness among students through various programs, implemented rules and regulations at Dayah Jamiiah Al-Aziziyah, and carried out strict monitoring and enforcement of regulations. All stages were executed carefully and meticulously to achieve the research objectives.